2020
DOI: 10.3390/antiox9100985
|View full text |Cite
|
Sign up to set email alerts
|

A Red Fluorescent Protein-Based Probe for Detection of Intracellular Reactive Sulfane Sulfur

Abstract: Reactive sulfane sulfur, including persulfide and polysulfide, is a type of regular cellular component, playing an antioxidant role. Its function may be organelle-dependent; however, the shortage of probes for detecting organellar reactive sulfane sulfur has hindered further investigation. Herein, we reported a red fluorescent protein (mCherry)-based probe for specifically detecting intracellular reactive sulfane sulfur. By mutating two amino acid residues of mCherry (A150 and S151) to cysteine residues, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Hm. denitrificans possesses two candidate transporters (SoxT1A and SoxT1B, Figure 1) encoded in close proximity to the genes encoding Sox proteins that are involved in the initial steps of thiosulfate oxidation and the genes for the cytoplasmic sHdr system (Li, Koch, et al, 2023;Li, Törkel, et al, 2023). However, evidence supporting the proposed sulfur transport has yet to be presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hm. denitrificans possesses two candidate transporters (SoxT1A and SoxT1B, Figure 1) encoded in close proximity to the genes encoding Sox proteins that are involved in the initial steps of thiosulfate oxidation and the genes for the cytoplasmic sHdr system (Li, Koch, et al, 2023;Li, Törkel, et al, 2023). However, evidence supporting the proposed sulfur transport has yet to be presented.…”
Section: Discussionmentioning
confidence: 99%
“…The polypeptides sHdrA and sHdrC2 as well as LbpA2 (aq_402) were identified, but were also present in the control sample (Table S4). Of the remaining proteins, 85 were associated with protein biosynthesis and degradation, and 24 were related to known or proposed functions of TusA other than sulfur oxidation, such as tRNA modification, molybdopterin cofactor biosynthesis and regulation (Dahl et al, 2013;Ikeuchi et al, 2006;Li, Törkel, et al, 2023). To gain further insight into the interaction partners of AqTusA, the re-purified samples were applied to SDS-PAGE (Figure 8a).…”
Section: F I G U R E 8 Re-purification Experiments Of Recombinantmentioning
confidence: 99%
“…These modifications may be induced specifically by sulfane sulfur, as other oxidative reagents, such as H 2 O 2 , organic peroxides, and disulfide, cannot induce the formation of multiple sulfur links between two Cys residues. This concept has been applied to design sulfane sulfur-specific fluorescence proteins which, due to the space restriction of the Cys residues involved, cannot form disulfide links, but can form trisulfide and tetrasulfide links [ 45 , 46 ]. Disulfide formation can be achieved by the induction of sulfane sulfur as well as H 2 O 2 and other oxidative reagents.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Liu et al reported two protein-based fluorescent probes for sulfane sulfurs: one based on green fluorescent protein (GFP) and the other based on red fluorescent protein (mCherry) [ 33 ]. They first carried out 3D structure analyses on the proteins and identified possible sites for mutation.…”
Section: Fluorescent Probes For the Detection Of Sulfane Sulfursmentioning
confidence: 99%